Al Azhar Student Profile Approach to Civic Disposition Development in Elementary Schools - Ramayani, Neti; Rafhi Febryan Putera; Ramadhanti, Adinda Asri; Zohro, Miftahus Silmi (Journal of Practice Learning and Educational Development, 2025)
This study aimed to examine the Al-Azhar Student Profile approach in developing citizenship character at the Elementary School level. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation studies at the Al-Azhar Islamic Education Foundation Elementary School. The results of the study indicate that the development of citizenship character is implemented through six main dimensions, namely Manners, Warrior Character, Scholarly, Skilled, Love for the Homeland and Global Insight, and Physically and Spiritually Healthy. This approach is implemented consistently through intracurricular, cocurricular, extracurricular activities, and school culture that shape religious values, nationalism, intelligence, 21st-century skills, and physical-spiritual balance. The conclusion of this study confirms that the Al-Azhar Student Profile provides a comprehensive and applicable framework in developing sustainable citizenship character in Elementary Schools, supported by synergy between schools, teachers, parents, and the environment.